Phylogenetic and Recombination Analysis of Tomato Spotted Wilt Virus - Lian, Sen; Lee, Jong-Seung; Cho, Won Kyong; Yu, Jisuk; Kim, Mi-Kyeong; Choi, Hong-Soo; Kim, Kook-Hyung (PloS one, 2013)
Tomato spotted wilt virus (TSWV) severely damages and reduces the yield of many economically important plants worldwide. In this study, we determined the whole-genome sequences of 10 TSWV isolates recently identified from various regions and hosts in Korea. Phylogenetic analysis of these 10 isolates as well as the three previously sequenced isolates indicated that the 13 Korean TSWV isolates could be divided into two groups reflecting either two different origins or divergences of Korean TSWV isolates. In addition, the complete nucleotide sequences for the 13 Korean TSWV isolates along with previously sequenced TSWV RNA segments from Korea and other countries were subjected to phylogenetic and recombination analysis. The phylogenetic analysis indicated that both the RNA L and RNA M segments of most Korean isolates might have originated in Western Europe and North America but that the RNA S segments for all Korean isolates might have originated in China and Japan. Recombination analysis identified a total of 12 recombination events among all isolates and segments and five recombination events among the 13 Korea isolates; among the five recombinants from Korea, three contained the whole RNA L segment, suggesting reassortment rather than recombination. Our analyses provide evidence that both recombination and reassortment have contributed to the molecular diversity of TSWV.